Genetic and molecular characterization of sublines obtained from the \"Galapagos enhanced trichomes\" genotype (MT-Get) and its relationship with the type-IV glandular trichome development pathway in tomato plants - Prants, Gabriela Simioni (2024)
Tomato glandular trichomes are pivotal due to their capacity in producing specialized metabolites. These metabolites prove effective against important herbivore pests. Since the genus Solanum has seven different types of multicellular trichomes, four of which are glandular types, tomato is an outstanding and complex model for studying trichome development. The type-IV is known for producing and exuding specialized metabolites called acylsugars. Acylsugars provide resistance to fungal pathogens and multiple insect pests, such as whiteflies. Domesticated tomato (S. lycopersicum) has low acylsugar production and greater vulnerability to insect predation. A tomato line derived from the wild species S. galapagense, called \"Galapagos enhanced trichomes\" (MT-Get), was developed to increase the density of trichome type-IV and clarify the development of those trichomes. Five chromosomal regions were mapped responsible for the formation of these trichomes. In this work, it was possible to obtain four isogenic sublines and analyze their contribution to the formation of trichome type-IV. The density of type-IV trichomes differed among the sublines. Chromosomal fragment 2, MT-Get02, was the most promising, being selected for a new cross with Woolly (Wo), an HD-ZIP IV transcription factor involved in trichome differentiation. It was possible to reduce the number of candidate genes for the formation of type-IV trichomes. The study explores the involvement of multiple genetic loci and highlights the need for further investigation to unravel the intricacies of the regulation and development of type-IV trichomes and their broader implications in defense mechanisms.